Outcome Study of Anterior Cervical Discectomy and Fusion with Lordotic Cage Insertion - Niljianskul, Nattawut (Journal of Health Science and Medical Research, 2022)
Objective: This study retrospectively evaluated the clinical and radiographic outcomes following the use of a lordotic cage in anterior cervical discectomy and fusion (ACDF). Material and Methods: All patients who underwent ACDF, at Vajira Hospital; between May 2017 and May 2020, were included in this study. Radiographic images were used to evaluate the device-level Cobb angle (DLCA), segmental Cobb angle (SCA), global Cobb angle (GCA), sagittal vertical axis (SVA), sagittal alignment (SA), and intervertebral disk height. The visual analog scale (VAS) for neck pain, and the Japanese Orthopaedic Association (JOA) score were reviewed as part of the patient’s medical records. Preoperative DLCA, SCA, GCA, SVA, SA, and intervertebral disk height measurements were compared with postoperative measurements at 1 year. Results: A total of 51 patients (88 disks), having undergone ACDF with lordotic cage insertion were included in this study. The initial curvature of the cervical spine was diagnosed as kyphosis in 30 (58.8%) patients, and as lordosis in 21 (41.2%) patients. There was significant improvement in the VAS, JOA, DLCA, SCA, GCA, SVA, SA, and intervertebral disk height after ACDF (p-value<0.050). In patients with preoperative kyphosis, the greatest changes were observed in the GCA (p-value=0.004). Conclusion: The use of a lordotic cage in ACDF improved both the clinical and radiographic outcomes of all postoperative parameters, regardless of the patient’s preoperative cervical spine curvature; although, patients with preoperative kyphosis had greater improvement in GCA.